Problem of optimal control for a determinate equation with interaction - Ostapenko, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
The problem of optimal control of differential equations with interaction is consider. It is proved that the optimal control satisfies the maximum principle and there exists the generalized optimal control. It is shown that, in the considered problem, new technical aspects arise as compared with the usual problem of optimal control.